A Magnetically Assembled High‐Aspect‐Ratio Needle Electrode for Recording Neuronal Activity. Issue 5 (15th January 2019) - Yasui, Taiki; Yamagiwa, Shota; Sawahata, Hirohito; Idogawa, Shinnosuke; Kubota, Yoshihiro; Kita, Yuto; Yamashita, Koji; Numano, Rika; Koida, Kowa; Kawano, Takeshi
Abstract: Microelectrode devices, which enable the detection of neuronal signals in brain tissues, have made significant contributions in the field of neuroscience and the brain–machine interfaces. To further develop such microelectrode devices, the following requirements must be met: i) a fine needle's diameter (<30 µm) to reduce damage to tissues; ii) a long needle (e.g., ≈1 mm for rodents and ≈2 mm for macaques); and iii) multiple electrodes to achieve high spatial recording (<100 µm in pitch). In order to meet these requirements, this study herein reports an assembly technique for high‐aspect‐ratio microneedles, which employs a magnet. The assembly is demonstrated, in which nickel wires of length 750 µm and diameter 25 µm are produced on a silicon substrate. The impedance magnitude of the assembled needle‐like electrode measured at 1 kHz is 5.6 kΩ, exhibiting output and input signal amplitudes of 96.7% at 1 kHz. To confirm the recording capability of the fabricated device, neuronal signal recordings are performed using mouse cerebra in vivo. The packaged single microneedle electrode penetrates the barrel field in the primary somatosensory cortex of the mouse and enables the detection of evoked neuronal activity of both local field potentials and action potentials. Abstract : Microelectrodes have made significant contributions in neuroscience. However, further improvements (e.g., fine diameter, long needle, and high‐density arrays) are required. To achieve such requirements, a microneedle assembly technique using a magnet is reported. The assembly of the nickel wires and in vivo neuronal recording capability of the fabricated microelectrode using mouse cerebra are demonstrated.